Characterisation and Antibacterial Activity of Green Tea Extract-Enriched Solid Goat's Milk Soap - Uswatun Chasanah; Dian Ermawati; Dwi Putri Utami; Angela Nora Hayati (Universitas Indonesia, 2022)
Solid goat's milk soap is organic and beneficial for the health and appearance of the skin. One of the components in green tea known to display antibacterial activities is epigallocatechin gallate (ECGC). In this study, the effects of solid goat's milk soap containing 1%, 2%, and 4% green tea extract on the growth of Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis were examined. The soap was characterized for its organoleptic, pH, free fatty acid, alkalinity, water content, foam stability, and hardness. In addition, an in vitro antimicrobial test was performed utilising the well-diffusion method. The findings revealed that all the soap formulas matched the SNI 3533-2016 standards for water content, free fatty acid content, and free alkali content, and that they also had similar pH, foam stability, and hardness. The solid goat's milk soap showed antibacterial activities against Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis, but the effect of the green tea extract on the soap did not increase these.